C-Fos activity in the insular cortex, nucleus accumbens and basolateral amygdala following the intraperitoneal injection of saccharin and lithium chloride. (24th April 2017) - Soto, Alberto; Gasalla, Patricia; Begega, Azucena; López, Matías
Highlights: Injected saccharin acts as an effective CS in the conditioned aversion preparation. Injections of saccharin and LiCl reduce voluntary consumption of the flavor CS. Intraperitoneal conditioning does not result in the production of aversive reactions. IP conditioning increases c-Fos activity in brain regions involved in CTA. Abstract: This study examined c-Fos expression in selected brain areas consequent to intraperitoneal (IP) administration of saccharin and lithium chloride. Rats were tested for aversion to the saccharin as measured by flavor consumption and orofacial reactions in the taste reactivity (TR) test. It was found that intraperitoneal conditioning resulted in the reduction in voluntary consumption but not in the production of aversive orofacial responses to the saccharin. The immunohistochemistry quantification revealed increased c-Fos activity in the insular cortex, the shell and core regions of the nucleus accumbens, and the basolateral nucleus of the amygdala. These results show that a conditioned taste aversion can be induced without direct oropharyngeal gustatory stimulation at the time of conditioning. In addition, this study provide evidence of increased neural activity in response to intraperitoneal saccharin injections.